Mapping employee readiness to return to work in the office after the pandemic in Indonesia - Simbolon, Hotpascaman; Artiwinata Ginting,; sipayung, Johansen; Aritonang, Christofel Martua; Napitupulu, Sarah Novita (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2024)
This research aims to see a picture of various industries and generations of workers responding to job changes with return-to-work activities in organizations (WFO). The method used in this research uses quantitative research using surveys (chairmanship). Sample data collection used a purposive sampling method, online, Google Forms, and offline, using a Likert scale. The research results involved a total of 121 respondents, with 43 male respondents and 73 female respondents, and those who did not provide information were 5 (five) people, where almost all of the respondents were from various regions or various company fields. Those mapped in this study are in the high category. It was found that management support aspects were not correlated with the control data on length of work and worker age.